Bioinspired Cellulase-Mimetic Solid Acid Catalysts for Cellulose Hydrolysis - Yang, Guangxu; Luo, Xiaolin; Shuai, Li (Frontiers in Bioengineering and Biotechnology, 2021)
Glucose produced by catalytic hydrolysis of cellulose is an important platform molecule for producing a variety of potential biobased fuels and chemicals. Catalysts such as mineral acids and enzymes have been intensively studied for cellulose hydrolysis. However, mineral acids show serious limitations concerning equipment corrosion, wastewater treatment and recyclability while enzymes have the issues such as high cost and thermal stability. Alternatively, solid acid catalysts are receiving increasing attention due to their high potential to overcome the limitations caused by conventional mineral acid catalysts but the slow mass transfer between the solid acid catalysts and cellulose as well as the absence of ideal binding sites on the surface of the solid acid catalysts are the key barriers to efficient cellulose hydrolysis. To bridge the gap, bio-inspired or bio-mimetic solid acid catalysts bearing both catalytic and binding sites are considered futuristic materials that possess added advantages over conventional solid catalysts, given their better substrate adsorption, high-temperature stability, and easy recyclability. In this review, cellulase-mimetic solid acid catalysts featuring intrinsic structural characteristics such as binding and catalytic domains of cellulase are reviewed. The mechanism of cellulase-catalyzed cellulose hydrolysis, design of cellulase-mimetic catalysts, and the issues related to these cellulase-mimetic catalysts are critically discussed. Some potential research directions for designing more efficient catalysts for cellulose hydrolysis are proposed. We expect that this review can provide insights into the design and preparation of efficient b